Socialization of stool color card for early detection of biliary atresia among healthcare professionals in Primary Healthcare facilities in Probolinggo - Setyoboedi, Bagus; Prihaningtyas, Rendi Aji; Utomo, Martono Tri; Akbas, Ahmad Maulana Ifan; Octariyandra, Syania Mega; Arief, Sjamsul (Caring: Jurnal Pengabdian Masyarakat, 2024)
AbstractBackground: Biliary Atresia (BA) is an idiopathic progressive fibro obliterative disease affecting the extrahepatic biliary duct with clinical manifestations of biliary obstruction in the neonatal period. Infants with BA are characterized with acholic stools which are frequently unidentified due to daily variations in stool color. Early detection is essential to reduce morbidity and mortality rates in infants with BA. Objective: This project aimed to improve the knowledge of health workers in primary health facilities in Probolinggo about BA through socialization of stool color cards as an early detection tool. Methods: Socialization was conducted to midwives in primary health facilities in Probolinggo with pre-test and post-test methods. Results: A total of 35 midwives participated in this activity. The evaluation showed a significant increase in health workers' understanding of biliary atresia. The average pre-test score was 83.82 and increased to 92.18 in the post-test with a p-value=0.00, indicating the effectiveness of counseling in improving health workers' knowledge. In addition, the implementation of the stool color card as an early detection tool received a positive response from the participants, who stated that the tool is easy to use and helps in identifying infants at risk of biliary atresia more accurately. Conclusion: The level of knowledge of health workers in primary health facilities regarding BA is still varied. Socialization of stool color cards may improve the understanding of health workers to accelerate early detection of cholestasis and improve the prognosis of infants with BA.